SOME ISSUES OF RURAL SETTLEMENTS POPULATION NUMBER AND RURAL SETTLEMENT TERRITORIAL STRUCTURE IN RA FRONTIER AREAS (Proceedings of the YSU C: Geological and Geographical Sciences, 2018)
The correlation analysis between rural settlements population number and their absolute height, cultivable land area, spatial and time distances from the nearest service centre have been given in the article. The revelation of regional differences and features of rural settlement in frontier areas has been highlighted through the analysis of transport-geographical location of settlements.
Keywords: frontier areas; population number of villages; cultivable lands; absolute height of settlements; nearest service centre; linear correlation